Improvement in the heating efficiency of fast ignition inertial confinement fusion through suppression of the preformed plasma. (25th April 2017) - Arikawa, Y.; Kojima, S.; Morace, A.; Hata, M.; Sakata, S.; Fujioka, S.; Kawashima, T.; Hironaka, Y.; Shigemori, K.; Abe, Y.; Zhang, Z.; Vaisseau, X.; et al.
Abstract: The study of fast electron spectrum optimization by suppression of preformed plasma in fast ignition targets is presented in this work. Integrated fast-electron spectra for electron energies below 3 MeV—the energy range responsible for core heating—are compared for different preformed plasma conditions. The pulse contrast (the ratio of peak-to-pedestal laser intensities) is compared for 10 8, 10 9 and 10 11 conditions at constant laser energy ( 500 J), pulse duration (2 ps), spot size (30% encircled energy on 50 µ m diameter) and laser intensity (around 1 × 10 19 W cm −2 ). The best electron spectrum optimization, consisting of maximized electron number for energies below 3 MeV was obtained with 14 µ m thick cone targets. The energy coupling efficiency from heating laser to core plasma, assuming typical core plasma parameters, was estimated to be 2%, although 0.37% was obtained with previous conditions with poor pulse contrast and a 7 µ m thick cone target.